Breaking cycles of subjugation through bodily performance: lived experience inside legal processes at the Marikana Commission of Inquiry - Robyn Gill-Leslie (Law Text Culture, 2021)
On 16th August 2012, the South African Police Service fired live ammunition into a crowd of striking mineworkers, killing 34 men and severely wounding others. Subsequently known as the Marikana massacre, the Marikana Commission of Inquiry was soon instituted to uncover the ‘truth’ about what had happened. This article suggests that such linear attempts at truth-finding excise bodily rhythms, resulting in a truth-finding exercise that risks redundancy and irrelevance for key stakeholders impacted by atrocity. Interrogating theoretical insights around corporeality, performance and rhythm to critique ideals of legal progress and aims of closure and truth exposition, this article uses encountered bodily performance as an analytical touchstone to reveal a parallel, cyclical rhythm inside the linear operation of the law. The article suggests that a prioritisation of such bodily performance – foregrounding the lived experience inside the law of truth-seeking – can make truth recovery more relevant to key stakeholders. Such bodily performance also demonstrates a pathway to breaking the cycle of bodily subjugation to positivist legal undertakings, by creating sensory bridges between key stakeholders inside the Marikana Commission of Inquiry.